2022
DOI: 10.3389/fphar.2022.882121
|View full text |Cite
|
Sign up to set email alerts
|

6-Gingerol attenuates subarachnoid hemorrhage-induced early brain injury via GBP2/PI3K/AKT pathway in the rat model

Abstract: Numerous studies have elucidated the neuroprotective effect of 6-gingerol in central nervous system diseases. However, the potential role and mechanism of 6-gingerol on early brain injury (EBI) after subarachnoid hemorrhage (SAH) remains poorly understood. Here, we report that 6-gingerol exerts a neuroprotective effect on SAH-induced EBI through the GBP2/PI3K/AKT pathway. A SAH rat model was established by injecting femoral artery blood into the cisterna magna. 6-gingerol or vehicle was injected intraperitonea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Reduced expression of Gbp2 modulated by C-34:6 may indicate pro-survival and anti-apoptotic mechanistic targets. Gbp2 protein levels increase after brain injury, and overexpression in neuronal cell types has been shown to aggravate neuronal apoptosis 36 . Additionally, decreased expression of C1qC was observed, which is involved in complement cascade activation.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced expression of Gbp2 modulated by C-34:6 may indicate pro-survival and anti-apoptotic mechanistic targets. Gbp2 protein levels increase after brain injury, and overexpression in neuronal cell types has been shown to aggravate neuronal apoptosis 36 . Additionally, decreased expression of C1qC was observed, which is involved in complement cascade activation.…”
Section: Discussionmentioning
confidence: 99%
“…We performed TUNEL experiments as previously described [19]. Apoptosis Detection Kit (Roche, United States) was used according to the manufacture's instruction.…”
Section: Tunel Assay and Nissl Stainingmentioning
confidence: 99%
“…Akt (also known as protein kinase B) is a key antiapoptotic signaling downstream of phosphoinositide 3-kinase (PI3K) that participates in a broad range of cellular processes. Mounting evidence has indicated that the activation of the Akt signaling pathway significantly improved neurological and cognitive functional outcomes [ 106 ] and contributed to the reduction in EBI and neuronal apoptosis after a SAH [ 107 ]. It is well established that Sirt1 interacts with Akt [ 108 ].…”
Section: The Therapeutic Role Of Sirt1 In Sahsmentioning
confidence: 99%